2018
DOI: 10.13040/ijpsr.0975-8232.9(10).4318-25
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The study carried out to find the effect of Aloe vera extract on the toxicity induced by INH -RIF in male Wistar albino rats. We have perform the experiments on rats for 30 days and found the effect on histological alternations of liver by two different method. Firstly, by Compound microscopy and the same tissues were further process through SEM microscopy. We have found the effect of Aloe vera extract and isoniazid and rifampicin on histological architecture of liver. We found that there is partial restoratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Hepatitis caused by isoniazid and rifampicin is linked to the death of cells in certain regions of the liver as well as centrilobular degeneration 21 . The study found isoniazid and rifampicin had been observed to produce hepatotoxicity in rabbit liver cells, and microscopic examination of these cells indicates inflammation and cell death at focal and centrilobular regions 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis caused by isoniazid and rifampicin is linked to the death of cells in certain regions of the liver as well as centrilobular degeneration 21 . The study found isoniazid and rifampicin had been observed to produce hepatotoxicity in rabbit liver cells, and microscopic examination of these cells indicates inflammation and cell death at focal and centrilobular regions 22,23 .…”
Section: Discussionmentioning
confidence: 99%